2024
DOI: 10.3390/app14052150
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Implant Number on Peri-Implant and Posterior Edentulous Area Strains in Mandibular Overdentures Retained by the New Ti–Zr (Roxolid®) Mini-Implants as Single-Units: In Vitro Study

Dario Puljic,
Asja Celebic,
Ines Kovacic
et al.

Abstract: The new Ti–Zr (Roxolid®) mini-implants have not yet been fully researched. We analyzed peri-implant and posterior edentulous area microstrains during mandibular overdenture (OD) loading at different sites with different extents of forces when one-, two-, three-, or four- mini dental implants (MDIs) as single-units supported the respective ODs. The models were designed from cone beam computed tomography (CBCT) scans of an appropriate patient with narrow ridges. The mucosal thickness was 2 mm. Strain gauges were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“…The explanation for the lower periimplant strains recorded in this study in the four-MDI model is that the loading forces were distributed and shared on more implants, thus reducing the strains around a single implant. The findings are similar to a recent study focused on the influence of a number of single-unit implants retaining an OD on peri-implant strains [54]. This study also showed that periimplant strains were higher in the models with two implants, regardless of the splinting status.…”
Section: Discussionsupporting
confidence: 91%
“…The explanation for the lower periimplant strains recorded in this study in the four-MDI model is that the loading forces were distributed and shared on more implants, thus reducing the strains around a single implant. The findings are similar to a recent study focused on the influence of a number of single-unit implants retaining an OD on peri-implant strains [54]. This study also showed that periimplant strains were higher in the models with two implants, regardless of the splinting status.…”
Section: Discussionsupporting
confidence: 91%